Psychosocial work stressors and risk of all-cause and coronary heart disease mortality: A systematic review and meta-analysis - Yamna Taouk; Matthew J Spittal; Anthony D LaMontagne; Allison J Milner (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVES: Psychosocial work stressors are common exposures affecting the working population, and there is good evidence that they have adverse health consequences. There is some evidence that they may impact on mortality, but this has not been systematically examined. We performed a systematic review, including risk of bias, and meta-analyses of observational studies to examine the association between psychosocial work stressors and all-cause mortality and death due to coronary heart disease (CHD). METHODS: Electronic databases were searched to identify studies and information on study characteristics and outcomes extracted in accordance with PRISMA guidelines. Risk estimates of outcomes associated with psychosocial work stressors: specifically, all-cause mortality, and death due to CHD were pooled using inverse variance weighted random effects meta-analysis. RESULTS: We identified 45 eligible cohort studies, of which 32 were included in the quantitative analyses of psychosocial work stressors and mortality. Low job control was associated with an increased risk of all-cause mortality [hazard ratio (HR) 1.21, 95% confidence interval (CI) 1.07-1.37, minimally-adjusted; HR 1.05, 95% CI 1.01-1.10, multivariable-adjusted; HR 1.03, 95% CI 1.00-1.06 exclusion of low quality studies and multivariable-adjusted] and CHD mortality [HR 1.50, 95% CI 1.42-1.58, minimally-adjusted; HR 1.23, 95% CI 1.17-1.30, multivariable-adjusted; HR 1.19, 95% CI 1.01-1.40, exclusion of low quality studies and multivariable-adjusted]. CONCLUSIONS: Workers with low job control are at increased risk of all-cause and CHD mortality compared to workers with high job control. Policy and practice interventions to improve job control could contribute to reductions in all-cause and CHD mortality.